2001
DOI: 10.1081/css-100103012
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Cotton Yield and Quality

Abstract: Precision agriculture technologies offer an opportunity to vary production inputs within a field. Variable rate application offers the potential to increase production efficiency and minimize potential adverse environmental effects of agricultural chemicals. As an initial step in the development of precision agriculture technologies for cotton, studies are needed to document variability of cotton. The primary objective of this study was to document variability of yield and quality of irrigated cotton within an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 13 publications
4
23
0
1
Order By: Relevance
“…In the study, 9 cotton breeding lines had higher values than the control variety 'GW-Teks' for this trait. Similar results were reported by Elms et al (2001) who observed average fiber length between 24-30 mm and the CVs for fiber length ranged from 2.3 to 4.2% in their studies. Fiber length is primarily determined by the variety, but is also influenced by temperature, water, nutrient stresses, and planting date (Elms et al, 2001;Davidonis et al, 2004).…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…In the study, 9 cotton breeding lines had higher values than the control variety 'GW-Teks' for this trait. Similar results were reported by Elms et al (2001) who observed average fiber length between 24-30 mm and the CVs for fiber length ranged from 2.3 to 4.2% in their studies. Fiber length is primarily determined by the variety, but is also influenced by temperature, water, nutrient stresses, and planting date (Elms et al, 2001;Davidonis et al, 2004).…”
Section: Resultssupporting
confidence: 78%
“…Similar results were reported by Elms et al (2001) who observed average fiber length between 24-30 mm and the CVs for fiber length ranged from 2.3 to 4.2% in their studies. Fiber length is primarily determined by the variety, but is also influenced by temperature, water, nutrient stresses, and planting date (Elms et al, 2001;Davidonis et al, 2004). Contradictory results can result from the cultivars having different genetic backgrounds and from changes in environmental conditions.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…These bolls tend to be less mature at harvest, and, therefore, have a lower value for micronaire under irrigation conditions (Davidonis et al. 1996, Elms et al. 2001, Pettigrew 2004).…”
Section: Resultsmentioning
confidence: 99%
“…For example, there is typically a ten fold wine grape yield variation across vineyards in any given year (Bramley & Hamilton, 2004). Spatial and temporal variability has also been reported in cotton (Elms et al, 2001;Meredith, 1996;and Wilkerson & Hart, 1996), corn (Chen et al, 2000;Krachenko et al, 2005;and Saddler et al, 2002), wheat (Ciha, 1984;Jin & Jiang, 2002;and Kelly et al, 2004), and vegetables (Barber & Raine, 2002).…”
Section: Spatial and Temporal Variability Of Crop Performancementioning
confidence: 97%